Social support, sense of belong, family functioning and life satisfaction - Chin, Ying Ying; Lim, Fang Yee; Tan, Kha Muan (2019)
This study examined the relations of social support, family functioning and sense of belonging and life satisfaction among the first year university students. The participants are 251 first year undergraduate students (88 males and 163 females) who aged from 18 to 25 with a mean age of 21.5 years (SD = 2.58) in Selangor state. We randomly collected the data from the public and private universities in Selangor to have a better understanding of life satisfaction among first year undergraduate students. The research tool is a quantitative survey that consists of demographic information, Sense of Belonging Instrument (SOBI), Family Assessment Device (FAD), Multidimensional Scale of Perceived Social Support (MSPSS), and Satisfaction with Life Scale (SWLS). The purpose to conduct this study was to fill the past research gap, to notify the society and to gain new insights about social support, family functioning, sense of belonging and life satisfaction. The present study found that family functioning and social support were significantly related to a university students’ life satisfaction. The university students with higher level of family functioning and social support tend to have higher level of life satisfaction. Moreover, the study also determined that the mediating role of sense of belonging in the relation of family functioning and life satisfaction as well in the path of social support and life satisfaction. First year undergraduate students with higher level of social support reported to have higher level of life satisfaction through the contribution of sense of belonging while the higher level of family functioning lead to higher level of life satisfaction through the contribution of sense of belonging. In conclusion, the present study has pointed out that life satisfaction among the first year university students can be determined by family functioning, social support and sense of belonging.